The Impact of Reuse Dialyzer Application on Routine Hemodialysis Patients Adequacy and Its Correlation with Cost Efficiency in Type D Hospital - Rulita Ayu Kusuma Ningtiyas (Academic Hospital Journal, 2021)
Background: Hemodialysis (HD) is one of the high cost service unit in the hospital which it implemented the cost effciency policy by the application of reuse dialyzer. According to claim recieved from Jaminan Kesehatan Nasional (JKN) system, the HD procedure for type D hospitals received the smallest claim payment if it compared to type A, B and C hospitals. This policy will be measured its effect on the effectiveness in the form of Ureum Reduction Ratio (URR) and Kt/V values and it associated with cost efficiency in type D hospital settings. Objectives The aims of this study were to 1.) Measure the corellation between the policy of using reuse dialyzer and the HD adequacy value and 2.) Evaluate the cost efficiency policy implemented by type D hospital HD unit in the form of using reuse dialyzer. Methods: This study was conducted with a cross-sectional design study from URR and Kt/V data on routine HD patients at 4 of type D hospital in Yogyakarta and Cantral Java in period Januari-March 2021. HD adequacy values were compared between the groups using the new and reuse dialyser. Cost efficiency was calculated based on the cost difference between cost of the HD procedure using a reuse dialyser and the projected cost if it is carried out with a single-use dialyzer.Result and Discussion: HD adequacy data were obtained from 112 subjects consisting of 22 with a new dialyzer, 32 with a reused (R) dialyzer first and R2, 27 with R3-R4 and 31 with R5-R7.The analysis of the effect of using reuse dializer on URR and Kt/V in the group with the new and reuse dialyser was obtained p = 0,90 and 0,91. The HD adequacy value in using reuse dialyser was not significantly different from using the new dialyser. The result of the cost efficiency analysis was 20.55% with using reuse dialyzer when it is associated with a source of income for HD services in type D hospitals.Conclusion: The application of reuse dialyzer is proved that it did not affect HD adequacy achievement when it compared to the use of a new dialyzer, and saved costs on HD services in type D hospitals. Keywords: Hemodialysis, reuse dialyzer, HD adequacy, efficiency